Artesunate inhibits type I interferon-induced production of macrophage migration inhibitory factor in patients with systemic lupus erythematosus. (January 2017) - Feng, X; Chen, W; Xiao, L; Gu, F; Huang, J; Tsao, B P; Sun, L
Objective: Macrophage migration inhibitory factor (MIF) is a key regulator of both atherosclerosis and systemic lupus erythematosus (SLE), yet factors leading to its overproduction remain unclear. To explore regulation of MIF in SLE, we studied effects and potential mechanisms of type I interferon (IFN) and artesunate (ART), an antimalarial agent extracted from Chinese herbs, on levels of MIF. Methods: Serum and peripheral blood cells from SLE patients and healthy controls were measured for MIF levels by ELISA and type I IFN-inducible gene expressions by real-time PCR, respectively, and assessed for associations by Spearman correlation. ART was added to human umbilical vein endothelial cell (HUVEC) cultures with or without prior IFNα-1b stimulation and to SLE peripheral blood mononuclear cell (PBMC) cultures. Protein levels of STATs and phosphorylated (p-) STATs in HUVECs were determined by Western blotting. Results: Serum MIF levels were elevated in SLE patients and positively associated with disease activity ( r = 0.86, p < 0.0001), accumulated damage ( r = 0.34, p < 0.05), and IFN scores in SLE PBMCs ( r = 0.74, p = 0.0002). The addition of IFNα-1b promoted MIF production in a time- and dose-dependent manner in HUVEC cultures. ART could inhibit expressions of IFN-inducible genes ( LY6E and ISG15 ) in both HUVEC and SLE PBMC cultures, and suppress MIF production and over-expression of p-STAT1, but not p-STAT3 or STAT5, induced by IFNα-1b stimulation. IFNγ-induced expression of p-STAT1 in HUVECs was not inhibited by ART. Conclusion: MIF could be regulated by type I IFN in SLE patients. ART counteracts the effect of IFNα to inhibit MIF production by blocking STAT1 phosphorylation and thus may have therapeutic potential for SLE-associated atherosclerosis.